Strong Earthquake-Prone Areas in the Eastern Sector of the Arctic Zone of the Russian Federation - Alexei D. Gvishiani; Boris A. Dzeboev; Boris V. Dzeranov; Ernest O. Kedrov; Anna A. Skorkina; Izabella M. Nikitina (Applied Sciences, 2022)
This paper continues the series of publications by the authors on the recognition of areas prone to the strongest, strong, and significant earthquakes using the FCAZ system-analytical method. The areas prone to earthquakes with M ≥ 5.5 in the eastern sector of the Arctic zone of the Russian Federation were recognized. It is shown that certain potential high seismicity zones are well confined to the boundaries of the Eurasian, North American, and Okhotsk tectonic plates. In addition, according to the results of the FCAZ recognition, some areas located at a sufficient distance from the main tectonic structures of the studied region were also recognized as highly seismic. The results of the study, among other factors, justify the use of the assessment of the completeness magnitude in the catalog for choosing the set of recognition objects for the FCAZ method.